Productive inefficiency in dairy farming and cooperation between spouses: Evidence from Senegal - Hoel, Jessica B.; Hidrobo, Melissa; Bernard, Tanguy; Ashour, Maha (International Food Policy Research Institute, 2017)
We examine productive inefficiencies in dairy farming in pastoralist house-holds in Northern Senegal, and using laboratory games, measure the relation-ship between spousal cooperation and productive inefficiency directly. In house-holds that behave less cooperatively in the games, cows owned by men produce10.6% more milk per day than cows owned by women, a gap that remainslarge and statistically significant after controlling for household, owner, andcow characteristics. Our results suggest that frictions between spouses mayindeed explain gender gaps in productivity, and support the use of lab-basedmeasures of household cooperation to complement survey data in explainingcollective behaviors.